A Survey to Assess Barriers to Urban Teaching Careers. (September 2016) - Creasey, Gary; Mays, Jennifer; Lee, Robert; D'Santiago, Verenice
The Urban Teaching Barriers survey was created to assess barriers to urban teaching careers. Pre-service teachers ( N = 377) completed this instrument, along with questionnaires that assessed urban teaching intentions and urban teaching self-efficacy. Six barrier domains were identified that tapped concerns over (a) lack of resources, (b) insufficient urban teacher preparation training, (c) cultural competency, (d) safety, (e) personal concerns, and (f) lack of support. The barrier subscales were differentially related to urban teaching intentions and teaching self-efficacy. These results as well as suggestions for future research are discussed.